PENGARUH PROFITABILITAS DAN KUALITAS AUDIT TERHADAP MANAJEMEN LABA DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Syarif M Helmi; Ahmad Kurniadi; Muhammad Khairul Anam; Soraya Nurfiza (Jurnal Akuntansi Trisakti, 2023)
The research was aimed to test and analyze the effect of profitability and audit quality on profit management moderated by company size. The type of research used is quantitative. The population in this study was sector companies listed on the Indonesia Stock Exchange in 2016-2020. In determining the sample of this study through purposive sampling technique obtained by 37 companies for five years and after going through outlier data, 141 data were obtained that were worthy of testing. The data analysis technique used moderated regression analysis with the help of SPSS 25 as a tool for testing. The results showed that profitability affects profit management, audit quality affects profit management, company size is unable to moderate the effect of profitability on profit management, and company size is able to moderate the impact of audit quality on profit management. The contribution of this research is to develop literature related to agency theory which is associated with the dependent variable and to provide information to companies and investors regarding the factors that can influence earnings management practices.